Improving the energy efficiency of built heritage in cold regions : Issues and opportunities - Luciani, Andrea; Nilsson, Kristina L.; Lidelöw, Sofia; Bhattacharjee, Shimantika; Örn, Tomas (Luleå tekniska universitet, Arkitektur och vatten, 2018)
The paper presents results from the research project “Smart energieffektivisering av kulturhistoriska byggnader i kallt klimat”. The research is expected to develop, test and assess methods and solutions to increase the energy efficiency of heritage timber buildings in the northernmost part of Sweden. The sub-arctic climate, with long, cold winters and mild summers, requires a significant use of energy, especially in historic buildings. This means that the difference in thermal performance and energy use with newly built buildings is greater and, at the same time, that even non-invasive interventions can be enough to save a considerable amount of energy with a limited impact on heritage values. Valuable timber buildings from the late 19th and early 20th century are analysed in the cities of Piteå, Malmberget and Kiruna. Results are based on data collected on their energy and thermal performances, on the analysis of their constructional features and on the assessment of their heritage value. ISBN för värdpublikation: 978-91-519-0838-0